Prevalence and significance of transient enteroenteric intussusceptions in children with recurrent colic abdominal pain - Plut Domen; Zupančič Živa (Srpski Arhiv za Celokupno Lekarstvo, 2020)
Introduction/Objective. Recurrent colic abdominal pain (RCAP) is a common complaint in children. Children with this complaint are often referred to abdominal ultrasound (US). Examining the children with RCAP by US in our outpatient clinic we occasionally noticed transient enteroenteric intussusceptions (TEIs) with spontaneous resolution. The objectives of our prospective observational study were to determine the prevalence and evaluate the significance of TEIs in children with RCAP. Methods. From January 2016 to December 2017 we examined 358 children with RCAP by US. Age range was 1–17 years (mean age 7.7 years). TEIs were detected and the prevalence determined. The sensation of pain at the time of the US examination was noted. Results. We detected TEI in 41 children; the prevalence was 11.5%. Abdominal pain at the time of the presence of TEI was reported in 17.1% of these children. In the group of children without TEI detected, pain at the time of the examination was reported in only 6%. A statistically significant relationship was found between the presence of TEI and the pain at the time of the examination (p = 0.046). No child had other significant abdominal pathology. Conclusion. TEIs happen more commonly in children than previously thought. A rather high prevalence of TEIs in our study group of children with RCAP and the fact that higher percentage of children with detected TEI experienced pain at the time of the examination, are suggestive that TEIs may be one of the causes for the RCAP in children.